Отечественная история. Российская империя в XVIII- XIX веках: учебное пособие - Афанасьев В. Г. Владимир Георгиевич; Позина Л. Т. Лариса Тихоновна; Севастьянов Ф. л. Федор Леонидович; Волошинова И. В. Ирина Валерьевна; Плюхина Т. В. Татьяна Витальевна; Соколов А. Р. Александр Ростиславович (СПб., Изд-во СПбГГИ, 2009)
Исключено из фонда НТБ ТПУ